Meeting report: the ALPHA project: a stakeholder meeting on lupus clinical trial outcome measures and the patient perspective. Issue 1 (14th February 2023) - Buie, Joy; Bloch, Lauren; Morand, Eric F; van Vollenhoven, Ronald F; Werth, Victoria P; Touma, Zahi; Lipsky, Peter; Kalunian, Kenneth; Askanase, Anca D; Ines, L; Reed, Christopher; Son, MaryBeth; et al.
Abstract : Drug development in lupus has improved over the past 10 years but still lags behind that of other rheumatic disease areas. Assessment of prospective lupus therapies in clinical trials has proved challenging for reasons that are multifactorial including the heterogeneity of the disease, study design limitations and a lack of validated biomarkers which greatly impacts regulatory decision-making. Moreover, most composite outcome measures currently used in trials do not include patient-reported outcomes. Given these factors, the Addressing Lupus Pillars for Health Advancement Global Advisory Committee members who serve on the drug development team identified an opportunity to convene a meeting to facilitate information sharing on completed and existing outcome measure development efforts. This meeting report highlights information presented during the meeting as well as a discussion on how the lupus community may work together with regulatory agencies to simplify and standardise outcome measures to accelerate development of lupus therapeutics.